Study of the benefit of solar energy through the management of photovoltaic systems in Colombia (2021)
One of the biggest problems in energy management is the impact on the environment. For this, it is necessary to propose new techniques and strategies which reduce pollution. Examples such as carbon dioxide and other greenhouse gas emissions promote an increase in the carbon footprint. This carries the search for resources from renewable sources as sunlight, wind, rain, waves, etc. From these sources, solar energy could be used in Colombia, especially the Atlantic Coast, due to high solar radiation in this region. This study is going to collect information about the advantages and disadvantages of using photovoltaic systems (PV systems) for solar energy management with a good cost-efficiency ratio. On the other hand, the development of solar energy will be studied and compared with other energy sources. In Colombia, there is a set of energy and regulatory policies around small self-generators with renewable energy sources, which can be natural or legal persons, that is, self-generators could be civilians, merchants, or small industries. Finally, it will be discussed about the energy plans as a proposal for improved energy management in the future.